Copyright issue on music back sound usage by Indonesian YouTuber - Xenia Angelica Wijayanto; Lestari Nurhajati (Universitas Negeri Yogyakarta, 2020)
According to We Are Social research in January 2018, Indonesia's population now is 265,4 million, while its social media active users reached 130 million. 43% of people are using Youtube as their primary social media. This situation shows us that Youtube is still the most used and liked social media channel, followed closely by Facebook and Whatsapp. The vlogger phenomenon is also getting stronger among Indonesian young people. The increasing number of Youtube content production ranged from artists, public figures, and ordinary people, also known as Youtuber. One of the famous Youtuber is Raditya Dika, whose subscriber reached more than 3.3 million, and estimated income per year around USD 46 thousand to USD 739 thousand. The problem that arises is about the copyright violation in background music used by Indonesian Youtuber. This research tries to dig further data about the youtube policy in protecting the copyright issue in that area. This research uses a discourse analysis method on 15 videos from the top 5 Youtuber in Indonesia as the unit of analysis. The result shows that some Youtuber still violate the copyright issue while using background music on their Youtube materials production.